2019
DOI: 10.1155/2019/9139145
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum IL-35 Levels and Bone Loss in Postmenopausal Women with Rheumatoid Arthritis

Abstract: Objective. IL-35 was reported as a crucial anti-inflammatory cytokine and could efficiently regulate bone metabolism in murine collagen-induced arthritis model. However, the relationship between IL-35 and bone health in human rheumatoid arthritis (RA) has not been clarified. In this study, the aim was to explore the correlations between IL-35 and bone loss in postmenopausal women with RA. Methods. The study included 76 postmenopausal women with RA and 53 healthy postmenopausal women as healthy controls (HCs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, it has not been fully understood whether IL-35 plays a role in skeletal system. In vivo study, IL-35 was confirmed to be positively correlated with bone mineral density, 25-(OH)VitD3 and be negatively correlated with b-isomerised carboxy-terminal crosslinking telopeptide of type I collagen, suggesting that IL-35 may be involved in the pathogenesis of skeletal system (17). Wanda Niedbala has confirmed that IL-35 can suppress the immune response by regulating the expansion of regular T cells and inhibiting the differentiation of Th17 cells (31).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, it has not been fully understood whether IL-35 plays a role in skeletal system. In vivo study, IL-35 was confirmed to be positively correlated with bone mineral density, 25-(OH)VitD3 and be negatively correlated with b-isomerised carboxy-terminal crosslinking telopeptide of type I collagen, suggesting that IL-35 may be involved in the pathogenesis of skeletal system (17). Wanda Niedbala has confirmed that IL-35 can suppress the immune response by regulating the expansion of regular T cells and inhibiting the differentiation of Th17 cells (31).…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, IL-35 was found to be involved in in multiple inflammatory diseases, autoimmune diseases and cancers, including type I diabetes, hepatitis, non-small cell lung cancer (14)(15)(16). Previous study also reported that IL-35 participated in bone metabolism (17,18). However, the possible mechanisms underlying this function have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prominent functions of IL-35 is the ability to propagate infectious tolerance and to generate a potent population of IL-35-expressing regulatory cells, which have been shown to exhibit immunosuppressive activity [ 99 , 100 ]. Functional analysis studies suggested that IL-35 plays a critical role in many autoimmune diseases such as multiple sclerosis (MS), systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and inflammatory bowel disease (IBD) [ 101 104 ].…”
Section: Immune System and Cytokinesmentioning
confidence: 99%
“…IL-35, a newly discovered heterodimeric cytokine and a member of the Interleukin (IL)-12 cytokine family ( Table 1 ) ( Li et al, 2019 ), consists of two subunits: α chain (p35) and β chain (EBI3) ( Kong et al, 2016 ). In detail, p35 had dissociation between p35 and p40 gene regulation ( Skrombolas et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have confirmed that IL-35, mainly secreted by immune cells, including the newly reported Breg cells (CD4+CD25+), had a high expression level in the bone marrow, thymus, blood and liver tissues ( Li et al, 2020b ; Zhang et al, 2020 ). Functional analysis suggested that IL-35 played a crucial role in many autoimmune diseases and allograft rejection, such as rheumatoid arthritis (RA) ( Li et al, 2019 ), multiple sclerosis (MS) ( Badihian et al, 2018 ), systemic lupus erythematosus (SLE) ( Ye et al, 2019 ), inflammatory bowel disease (IBD) ( Su et al, 2018 ), psoriasis and experimental autoimmune uveitis (EAU) ( Zhang et al, 2016 ). What’s more, it has been confirmed that IL-35 had a higher expression level in chronic hepatitis patients and its expression level had a positive association with the severity of infection ( Dong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%